STRATEGI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KEBERHASILAN PROGRAM TAHFIDZ AL-QUR’AN DI SMP AL-FATIMAH BOJONEGORO - Fitri Dwi Zuhrotun Nisa; Sedya Santosa; Raisa Zuhra Salsabila Awaluddin (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
This research discusses Human Resource Management (HRM) strategies in improving the success of the Qur'an Tahfidz program at SMP Plus Al-Fatimah Bojonegoro. The purpose of this study is to identify the process of recruitment, selection, development, and supervision of educators who are effective in supporting program implementation. The research used a descriptive qualitative approach with data collection through observation, interviews, and document analysis. The results showed that a careful recruitment and selection process, accompanied by continuous training, succeeded in improving the pedagogical competence and ability of teachers in delivering Tahfidz materials. In addition, the application of innovative learning methods such as the Ummi method and periodic evaluations ensure the effectiveness of learning and the achievement of students' Qur'an memorization. The study concludes that the implementation of integrated HR management not only supports the success of the flagship program, but also creates an educational environment conducive to character building, skills development and improving the quality of graduates. The findings confirm the importance of strategic HRM in supporting the sustainability and positive image of educational institutions.